A Story of Pathology and Cancer - Mohammad Zulkarnaen, Bin Ahmad Narihan (UNIMAS Publisher, 2020)
The main purpose of this book is to introduce the history of pathology, the features of cancer from the pathological aspect and the role of pathology in the medical advances of cancer. However, it does not intend to provide an exhaustive discussion on cancer. It is a compilation of results to some of the research findings that has been undertaken so far.